Effect of cowpea (Vigna unguiculata) and Dolichos lablab (Lablab purpureus) hay supplementation on ammonia concentration and microbial-N supply in calves fed tef (Eragrostis tef) straw - Ebro, A.; Umunna, N.N.; Yami, A.; Nsahlai, I.V. (Ethiopian Society of Animal Production, 1995)
Two trials on rumen ammonia concentration and amount of microbial nitrogen supplied were conducted at the International Livestock Research Institute, Debre Zeit Station, with calves fed a basal diet of tef (Eragrostis tef) straw supplemented with three levels of Cowpea (Vigna unguiculata) or Lablab (Lablab purpureus) hay. The supplements were fed at 0.5, 1.5 percent of the body weight of the calves. In trial one, twenty one calves were randomly assigned to one of the dietary treatments mentioned above. In the metabolism trial, thirty male calves blocked on age were used. The result indicated that the effect of supplement type x level interaction, supplement type and increasing level of the supplements on ammonia concentration was not significant. Rumen ammonia concentration increased in response to supplementation. Supplementation increased the urinary excretion of allantoin, uric acid, total purine derivatives (allantoin + uric acid) and the amount of microbial nitrogen supplied. The supplement types did not differ in terms of their effect on any of the variables studied. Therefore, it is concluded that cowpea and lablab hay had a similar effect on the variables studied indicating the possibility of using either of the two legumes as a supplement.